Periosteal Graft Myringoplasty: Our Experience - ElTaher,Mostafa (2018)
Abstract Introduction Different types of autologous graft materials are used for myringoplasty, with the temporalis fascia and cartilage being the most frequently used tissues. Periosteal tissue has been used for a long time in our department, and many advantages support its use in myringoplasty. To the best of our knowledge, this issue is scarcely discussed in the previously published literature. Objective To present our experience with periosteal graft myringoplasty, describing the technique and the anatomical and functional outcomes. Methods A prospective clinical study involving 88 patients (72 females and 16 males) with a mean age 26.9 years. The patients underwent myringoplasty using the mastoid cortex periosteum; they were all operated using the postauricular approach, and the graft was applied using the underlay technique. The patients performed pre- and postoperative pure tone audiometry for tested frequencies (0.5 kHz, 1 kHz, 2 kHz, and 4 kHz). All patients were followed-up for at least 12 months after the operation. Results The anatomical success rate among all patients was of 93%, which is comparable to the rate of success in procedures using other usual grafting materials. In addition, there was a highly significant postoperative improvement in pure tone audiometry results as compared with the preoperative ones (the main hearing gain was of ∼ 11 dB; p< 0.001). Conclusion The periosteal graft is easily harvested, easy to apply, with excellent anatomical and functional success.